Investigation of the Gracilaria gracilis proteome response to nitrogen limitation - Naidoo, René Kathleen (Department of Molecular and Cell Biology, 2015)
Gracilaria gracilis, a commercially important red macroalgal species found on the west coast of South Africa, is one of two Gracilaria species used in the production of hydrocolloid agar. In the past, commercial quantities of G. gracilis were harvested from Saldanha Bay until population collapses of the natural resource necessitated the need for research into alternative aquaculture programs for G. gracilis cultivation. One of the reasons for the G. gracilis population collapse was attributed to adverse conditions during summer which led to thermal stratification of the water column and subsequent nutrient limiting conditions. Inorganic nitrogen has been identified as the major nutrient factor limiting growth and production of G. gracilis populations in South Africa. Although the physiological mechanisms implemented by G. gracilis which allow adaption to low nitrogen environments have been investigated, not much is known about the molecular mechanisms which underlie these adaptions. Thus, it is necessary to elucidate the molecular basis of these adaptions in G. gracilis to complement the existing physiological data. In this study, a differential proteomics approach employing two-dimensional gel electrophoresis and liquid chromatography tandem mass spectrometry was used to investigate G. gracilis proteome changes in response to nitrogen limitation and recovery. Putative identities of 22 proteins that were changed significantly (P<O.05) in their abundance in response to nitrogen limitation and recovery were obtained. The identified proteins functioned in a range of biological processes including glycolysis, photosynthesis, A TP synthesis, galactose metabolism, protein-refolding and biosynthesis, nitrogen metabolism and cytoskeleton remodelling. A detailed discussion proposing the possible role(s) of each putative G. gracilis protein, along with the associated metabolic pathways activated or repressed in response to N stress, is provided. Fructose 1, 6 biphosphate aldolase and glutamine synthetase were selected for further validation and characterisation studies. The identities of these enzymes were confirmed by western blot analysis. Additionally, the decreased abundance of fructose 1, 6 biphosphate aldolase during nitrogen limitation observed with two-dimensional gel electrophoresis analysis was validated by enzymatic and western blot analysis. The over-expression of fructose 1, 6 biphosphate aldolase and glutamine synthetase determined with two dimensional gel elctrophoresis during nitrogen recovery was not validated by western blot analysis. Re-supply of nitrogen to nitrogen limited G. gracilis elicited small changes in protein abundance that were not significant (P<O.05) due to the large degree of biological variation between seaweed samples. The effect of nitrogen limitation and recovery on theenzyme activity of pyruvate kinase was investigated. The enzyme activity of pyruvate kinase, a key enzyme integrating carbon and nitrogen metabolic pathways, did not respond to nitrogen limitation and recovery. The effect of nitrogen limitation on G. gracilis carbon allocation patterns was briefly investigated. Intracellular G. gracilis starch levels were observed to markedly increase during nitrogen limitation This increase, combined with the decreased abundance of a number of glycolytic proteins, suggests that a change in carbon allocation patterns occurs in G. gracilis in response to nitrogen limitation. To the best of our knowledge this study provides the first characterisation of G. gracilis proteome changes in response to nitrogen limitation and subsequent recovery. The identification of key proteins and pathways involved in the G. gracilis nitrogen stress response has provided an insight into the adaptions implemented by G. gracilis to cope with nitrogen limitation. The results of this study reinforce the relationship between carbon and nitrogen metabolism since the majority of the identified proteins are involved in glycolytic and photosynthetic processes.